Enhancement of the cryogenic‐interfacial‐strength of carbon fiber composites by chemical grafting of graphene oxide/attapulgite on T300. Issue 12 (17th August 2020) - Yan, Meiling; Jiao, Weicheng; Li, Jun; Huang, Yifan; Chu, Zhenming; Chen, Xiaodan; Shen, Feng; Wang, Yong; Wang, Rongguo; He, Xiaodong
Abstract: A mismatch between the expansion coefficients of carbon fiber (CF, T300) and resin causes thermal deterioration at the interface of composite cryotanks. This study presents an effective method to enhance the cryogenic interfacial properties of a T300/epoxy (EP) composite, in which graphene oxide (GO)/attapulgite (ATP) hierarchical structures are chemically grafted onto the surface of T300. GO and ATP were sequentially assembled on the T300 surface, which changed the morphology of T300 and optimized the interfacial wettability of T300/EP. Surface topography and chemical bonding of grafted T300 fibers (T300‐GO‐ATP) were evaluated by SEM and XPS, respectively. Considering the functioning conditions of composite cryotanks, three cryogenic interfacial testing conditions were designed for the T300‐GO‐ATP/EP composites: −196°C, cryogenic cycling (from RT to −196°C), and immersion in liquid nitrogen (LN2 ). The interfacial shear strength (IFSS) of T300‐GO‐ATP/EP composite at −196°C was 88.3 MPa, 53.1% stronger than that of T300/EP (57.6 MPa). Likewise, the IFSS of T300‐GO‐ATP/EP composites was tested under cryogenic cycling/immersion in LN2, which increased remarkably comparing to those of T300/EP under the same conditions. Results shows that GO/ATP suppress interfacial cracking and enhances the interfacial bonding of T300/EP at cryogenic temperatures through chemical bonding and nanointerlocking. Abstract : Enhancement of CFRP's cryogenic‐interfacial‐strength by T300‐GO‐ATP.